2006
DOI: 10.1021/jf061191d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Peptide in Enzymatic Hydrolyzate of Cheese That Inhibits Ovalbumin Permeation in Caco-2 Cells

Abstract: Because the first step in the triggering of food allergy is the permeation of the allergen through the intestine, enhancement of the intestinal barrier function is thought to be effective for preventing food allergy. In this study, a peptide that inhibits ovalbumin (OVA) permeation in an in vitro Caco-2 cell model was isolated from enzymatic hydrolyzate of cheese (EHC). Amino acid sequence analysis identified the active peptide as GPIVLNPWDQ, a sequence identical to amino acids 102-111 of alphas2-casein. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
(33 reference statements)
1
20
0
1
Order By: Relevance
“…We have reported that NPWDQ (aa 107-111 of s 2 -casein), which occurred in the EMC, inhibited OVA permeation in a Caco-2 cell model. 10) In this study, first we examined to determine whether NPWDQ would inhibit the permeation of FITC-dextran (a marker of paracellular transport 18) ) and HRP (that of transcellular transport 18) ) in vitro. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have reported that NPWDQ (aa 107-111 of s 2 -casein), which occurred in the EMC, inhibited OVA permeation in a Caco-2 cell model. 10) In this study, first we examined to determine whether NPWDQ would inhibit the permeation of FITC-dextran (a marker of paracellular transport 18) ) and HRP (that of transcellular transport 18) ) in vitro. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Denmark skim cheese was hydrolyzed with Protease S, Newlase A, and Umamizyme (Amano Enzyme, Nagoya, Japan), as reported previously. 10) Briefly, Denmark skim cheese was suspended in water (50% w/v), and then the proteases were added to a final concentration of 0.15-0.3% (w/v). EMC was obtained after Protease S treatment at 34 C for 48 h, followed by Newlase A/Umamizyme treatment at pH 4.1 at 34 C for 120 h. The resulting EMC was heat treated at 110 C for 10 min to inactivate the enzymes used in the preparation, and freeze-dried.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…62) Amino acid sequence analysis identified the active peptide from the EHC as GPIVLNPWDQ, a sequence identical to aa102-111 of s 2 -casein. 63) This decapeptide significantly inhibited OVA permeation at a concentration of 10 À6 M. It was also found that a pentapeptide half, NPWDQ, is essential to the inhibitory activity, since NPWDQ, but not GPIVL, had nearly the same inhibitory activity as GPIVLNPWDQ. 63) The results suggest a novel point concerning the significance of lactation in preventing protein (allergen) permeation in the small intestine, since this kind of peptide would be produced from casein by proteases in the infant digestive tract, and its production might prevent allergen permeation.…”
Section: Inhibition Of Allergen Permeation At the Intestine To Prevenmentioning
confidence: 83%